Free will, determinism and the "problem" of structure and agency in the social sciences - Pleasants, Nigel (2019)
The so-called (3z(Bproblem(3y (Bof structure and agency is clearly related to the philosophical problem of free will and determinism, yet the central philosophical issues are not well understood by theorists of structure and agency in the social sciences. In this article I draw a map of the available stances on the metaphysics of free will and determinism. With the aid of this map the problem of structure and agency will be seen to dissolve. The problem of structure and agency is sustained by a failure to distinguish between metaphysical and empirical senses of the relation between social structure and individual agency. The ramifications of this distinction are illustrated via a case study of competing explanations of perpetrator behavior in Christopher Browning$1 (Bs and Daniel Goldhagen$1 (Bs studies of the German Order Police in the Holocaust. - Reproduced.s
Keywords: Structure and agency